GENDER DISPARITY IN RISK FACTORS FOR CHRONIC KIDNEY DISEASE IN A RURAL COMMUNITY IN SOUTHERN NIGERIA - Okoye OC (Ntec Specialist, 2020)
Background: The evidence for gender disparity in prevalence of CKD is conflicting; while some studies report male preponderance, others have reported female preponderance or no difference. Reasons for gender disparities in CKD prevalence may be related to differences in the occurrence of risk factors across the gender, amongst other factors. This study was to determine gender disparities in the risk factors for CKD. Method: This study is based on data from a community based cross-sectional study carried out in Ogbona, a rural community in Southern Nigeria. The WHO STEPS for surveillance of chronic diseases risk factors and chronic disease-specific morbidity and mortality questionnaire was adapted for this study. Four hundred and seventy-six participants were selected from 142 housing units in the community using multi-stage cluster sampling. Clinical examinations and laboratory investigations including serum creatinine, and urinalysis were performed. Results: Majority of participants were females (66.2%). CKD was commoner in females compared to males (14.3% vs. 12.7%, P= 0.06). More females than males had high body fat percentages (65.7% vs. 40.9%, P less than 0.0001), high waist-hip ratio (99.7% vs 73.3%, P less than 0.0001) and central obesity (43.1% vs. 4.3% P less than 0.0001). More males compared to females used alcohol (56% vs. 9.2%, P less than 0.0001), were overweight (42.2% vs 28.9%, P=0.004), and had proteinuria (6.2% vs 2.5%, P=0.054). The odds of females having central obesity are 16.7 times the odds of males having central obesity; similarly, the odds of females having high BF are 2.7 times the odds of males having high BF. Females had 122-fold the odds of men having high WHR. The odds of drinking alcohol are 92% less compared to males. There were no statistically significant gender differences regarding hypertension, diabetes mellitus, and use of nephrotoxins (NSAIDS, skin lightening agents, herbal medications). No female smoked cigarettes. Conclusion: This study shows that there is no statistically significant gender difference as regards prevalence of CKD, however several risk factors of CKD show gender disparity. The odds for central obesity, high WHR, high body fat percentages are significantly greater in females; while smoking, alcohol use, and overweightedness, are commoner in males. There were no statistically significant gender differences regarding hypertension, diabetes mellitus, and use of nephrotoxins (NSAIDS, skin lightening agents, herbal medications)